2015
DOI: 10.1128/jvi.03456-14
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Receptor Binding Preferences of Recombinant Hemagglutinins from Avian and Human H6 and H10 Influenza A Virus Subtypes

Abstract: During 2013, three new avian influenza A virus subtypes, A(H7N9), A(H6N1), and A(H10N8), resulted in human infections.While the A(H7N9) virus resulted in a significant epidemic in China across 19 provinces and municipalities, both A(H6N1) and A(H10N8) viruses resulted in only a few human infections. This study focuses on the major surface glycoprotein hemagglutinins from both of these novel human viruses. The detailed structural and glycan microarray analyses presented here highlight the idea that both A(H6N1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…Consistent with the findings of many research groups (29,45,(47)(48)(49), we found that JX/13 exhibits a strong preference for ␣2,3-linked sialic acids with minimal binding to ␣2,6-linked sialic acids. Based on the structure of the HAs from A/mallard/Sweden/51/ 2002 (H10N2) and JX/13, Vachieri et al postulated that the mutation K137R in JX/13 may further enhance binding to ␣2,6-linked sialic acids (46).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the findings of many research groups (29,45,(47)(48)(49), we found that JX/13 exhibits a strong preference for ␣2,3-linked sialic acids with minimal binding to ␣2,6-linked sialic acids. Based on the structure of the HAs from A/mallard/Sweden/51/ 2002 (H10N2) and JX/13, Vachieri et al postulated that the mutation K137R in JX/13 may further enhance binding to ␣2,6-linked sialic acids (46).…”
Section: Discussionsupporting
confidence: 92%
“…While the receptor-binding preference of JX/13 has been the subject of extensive research, ours is the first report to characterize the binding preferences of a panel of diverse H10 isolates. In previous studies, A/green wing teal/Texas/Y171/2006 (H10N7) was shown to have a strong preference for ␣2,3linked sialic acids, with no binding to ␣2,6-linked sialic acids (45), while A/mallard/ Sweden/51/2002 (H10N2) was shown to display a ␣2,3-linked sialic acid binding preference with some binding to ␣2,6-linked sialic acids (46). Our findings that H10 isolates displayed a range of binding profiles to ␣2,6-linked sialic acids reconcile these conflicting reports.…”
Section: Discussionmentioning
confidence: 98%
“…3A and Table S1). Interestingly, the virus production rates of these variants in LMH cells were related to the NA activity on 3-SLN, which is an avian receptor (13) (Fig. 3B), suggesting that glycosylation on NA affected IAV replication in mammal and avian cells differently ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an avian H10N7 strain was found to be the etiological agent responsible for the massive die-off harbor seals in the Baltic Sea, an epidemic that killed more than 10% of the local seal population (4)(5)(6). The receptor binding profile of H10 viruses is currently debated (7)(8)(9)(10)(11)(12), but the subtype has been proven to cause productive infections in humans (13,14). Currently, the only treatment option for patients infected with an H10 subtype influenza virus is the use of antiviral inhibitors that target the viral neuraminidase (NA).…”
mentioning
confidence: 99%